Implementation of Ensemble Deep Learning for Brain MRI Classification in Tumor Detection - Syam, Rahmat Fuadi (yocto brain, 2025)
Introduction: Brain tumor detection from MRI images is critical for early diagnosis and treatment planning. While individual deep learning models have shown high accuracy in medical image classification, combining multiple models can potentially enhance performance. This study aims to develop an ensemble deep learning framework using ResNet18 and DenseNet121 to improve the accuracy of brain tumor classification. Methods: A dataset of 7,023 brain MRI images categorized into four classes—glioma, meningioma, no tumor, and pituitary tumor—was used. Pre-processing included resizing to 224×224 pixels, normalization, and augmentation (random flipping and rotation). ResNet18 and DenseNet121 models were fine-tuned separately using the Adam optimizer with a learning rate of 0.001. The ensemble method was implemented by averaging the softmax outputs of both models to generate final predictions. Results: When evaluated individually, ResNet18 and DenseNet121 achieved validation accuracies of 97.72% and 97.79%, respectively. The ensemble model significantly outperformed both, reaching a validation accuracy of 99.36%. This result demonstrates that integrating both architectures effectively reduces misclassification and enhances overall robustness. Confusion matrix analysis confirmed high classification accuracy across all four tumor categories. Conclusions: The proposed ensemble deep learning approach successfully leverages the strengths of ResNet18 and DenseNet121, achieving superior classification accuracy for brain tumor detection in MRI images. This method holds promise as a reliable tool in clinical diagnostic workflows. Future research should focus on integrating additional architectures, advanced augmentation strategies, and hyperparameter optimization to further improve performance